DEVELOPMENT OF PROJECT-BASED LEARNING (PJBL) BASED MATHEMATICS MODULES ON COMPARISON MATERIALS - Asiana, Nur Rul; Kurniawati, Naning; Fitri, Anisa (Tesseract: International Journal of Geometry and Applied Mathematics, 2024)
Learning process that takes place definitely requires a teaching material. Teaching materials are needed that can facilitate student in ongoing learnings processed. One planner and designedly learnings experiences to helped student's masters’ learnings of them is using the learnings method in the forms of the learnings module. Modules is a formed of teachings materials that's is packages in a complete and systematically manners whichever containing a set of objectively. The module is arranged Project Based Learning (PjBL) method. The purposes of this studying are to determine the validitys and Practicalities of the developer’s mathematics modules. The types of researchers conducted was Research and Development (R&D) used the ADDIE models developments methods (analysist, designed, developments, implementations, and evaluations). Location This researcher took place at SMP Plus Al Hadi with class VII students as researchers subjects. The datas analysist techniques uses is Quantitative in the former of validity analysist and practicality analysis. The resulted of the researchers shows that's the developed module is valid and practical. The mathematics modules declare validates bases on the Validations resulting from media's exports and materials experts. The resulted of validation by media's expert's Obtained a value of 75% (valid) and the resulted of Validation by materials expert's Obtained a value of 82.69% (valid). After beings validates, the modules are then texted on students to find out the Practicality of the module. There trials were carrier outs in two's states, nameless a limiters scale trial and a large-scale trial. In the limiter trials phases, a value of 84.58% (p-tactical) was obtained and in the large-scale trial stage, a value of 86.29% (very practical) was obtained. Thusly, it's Can's he concludes that's the developed PjBL-based mathematics module it's suitably fors used in learnings.